Legalized prostitution in Germany: inside the new mega brothels - Staiger, Annegret Daniela (Indiana University Press, 2022)
"Germany has been infamously dubbed the 'Brothel of Europe,' but how does legalized prostitution actually work? Is it empowering or victimizing, realistic or dangerous? In Legalized Prostitution in Germany, Annegret Staiger's ethnography engages historical, cultural, and legal context to reframe the brothel as a place of longing and belonging, of affective entanglements between unlikely partners, and of new beginnings across borders, while also acknowledging the increasingly exploitative labor practices. By sharing the stories of sex workers, clients, and managers within the larger legal system-meant to provide dignity and safety through regulation-Staiger skillfully frames the economic aspects of commercial sex work and addresses important questions about sexual labor, intimacy, and relationships. Weaving insightful scholarship with beautiful storytelling, Legalized Prostitution in Germany provides readers with a deeper understanding of the complexities of legalized prostitution."--